The role of corporate merger in achieving synergy (Analytical research in a sample of companies of the Iraqi Ministry of Industry and Minerals) - Khalaf, Amin Zedan; Said, Abdel Salam Lefta (Journal of Economics and Administrative Sciences, 2021)
The research aims to shed light on the recent experience in the Iraqi business environment, which is the experience of the merger. To evaluate a recent experience in an important sector of the Iraqi business sectors, namely the industrial sector to enable decision-makers to review that experience to judge the extent of its success and address some of the lapses that experience that by measuring synergies can be judged on the success of the merger experience or not. The research community is the governmental industrial sector. The research sample included six cases of merger (14) companies before the merger. The Holt method was used to predict the net sales and total cost values ​​before the merger as if it were not merged. The researcher reached a number of conclusions, the most important of which is that the merger achieved cost synergies for all cases of merger, and other conclusions were achieved synergistic net sales of part of the merger cases such as the General Company for Steel Industries and the General Company for Food Industries Companies that did not achieve consistency in net sales, as well as there are points of failure in the merger of the General Company for Electrical Industries, the General Company for Metallurgical Industries, the General Company for Design and Execution of Projects and the General Electronic Systems Company for not achieving synergies at the level of net sales